UTILIZATION OF ONLINE LEARNING MEDIA IN LEARNING PHYSICS IN THE MADIUN RESIDENCY DURING THE COVID19 PANDEMIC - Andista Candra Yusro; Putri Nadia; L Lukesi; Oktavia Nur Insan; Daffa Mahendra; Muhammad Adam (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
This study aims to determine the implementation of physics learning in schools during the implementation of the covid 19 pandemic. This research was conducted using a survey method with a population of physics teachers in the Madiun residency. The determination of the survey sample was carried out by random sampling. Based on the survey results, it was found that 87% of teachers used google classroom, and the remaining 13% used virtual face-to-face (zoom and G-meet) and social media such as youtube and Whatsapp groups. Meanwhile, 90% of these teachers conduct learning independently, not centrally facilitated by the school. This fact results in learning monitoring cannot being carried out properly. Teachers at school need additional knowledge related to online learning platforms, especially those that can be used easily in learning physics at school.